Domestic bliss, or technological diss? Problematic media use, partner responsiveness, and relationship outcomes. (December 2021) - Booth, McCall A.; Coyne, Sarah M.; Yorgason, Jeremy B.; Dew, Jeffrey P.
The purpose of this study was to examine how problematic media use (technoference, internet gaming disorder symptoms, and pornography use) predicted later partner relationship outcomes, operating through the mediator of partner responsiveness. Participants ( N = 1039) were from Waves II–IV of a nationally representative quantitative study on marriage relationships across the United States. Both spouses completed surveys reporting problematic media use, partner responsiveness, and relationship outcomes at three separate time points each spaced a year apart. In order to test the hypotheses, three longitudinal actor-partner interdependence models with indirect paths were estimated, with each model corresponding to one type of problematic media use. Results indicated that at the cross-sectional level, all three types of problematic media use had significant indirect actor and partner effects, where problematic media use predicted lower relationship outcomes through the intervening variable of partner non-responsiveness. Longitudinally, wife technoference directly negatively predicted later partner responsiveness, but there were no full indirect paths of Wave II problematic media to Wave IV relationship outcomes through the intervening variable of Wave III partner responsiveness. Implications of these findings and future directions are discussed.